PENYULUHAN TENTANG MANFAAT DAUN NIPAH UNTUK PENYEMBUHAN SAKIT GIGI DI PUSKESMAS PB. SELAYANG II - Zola Efa Harnis; Anggun Syahfitri; Sulasmi Sulasmi; Silmi Hayati (Jurnal Pengabdian Masyarakat Putri Hijau, 2021)
The nipah plant (nypahfruticans) has been commonly used as an ingredient in traditional medicines such as stomach aches, diabetes, internal febrifuge, toothache medicine and headache medicine. The nipah plant (nypahfruticans) is efficacious as a sinusitis medicine, in addition to the nipah plant extract (nypahfruticans) is able to inhibit tuberculosis, liver disease (liver), sore throat is also efficacious as a carminative (can help the body's wind discharge), antidote and medicine tranquilizer. This counseling aims to obtain counseling data about the benefits of nipah leaves for healing toothaches at the PB Health Center. Brief II. Counseling was carried out with an interactive method between the presenters and participants so that the event took place in an interesting manner and provided education to the community about the benefits of nipah leaves as a toothache treatment at PB Selayang II. The results obtained from this counseling are lack of understanding or lack of knowledge of the community following the counseling at PB. Selayang II about the use of nipah leaves as a toothache treatment, by providing guidance and assistance with counseling methods, the results were obtained where the community, especially those who took part in the counseling, showed enthusiasm in curiosity about the benefits of nipah leaves as a toothache treatment as well as increased experience and knowledge of the people of PB. Selayang II who participated in counseling the benefits of nipah leaves as a treatment for toothaches through materials and simulations obtained during socialization. The conclusion of this counseling the community has been able to know the benefits of nipah leaves as a toothache treatment.